Pengaruh Independensi, Kompetensi, Dan Pengetahuan Terhadap Kualitas Audit Pada Kantor Akuntan Publik Di Kota Denpasar - I Made Putra Juliantara; Ni Wayan Alit Erlina Wati; Putu Cita Ayu (Hita Akuntansi dan Keuangan, 2026)
This study emphasizes that ensuring audit quality is fundamental to upholdingintegrity of financial statements while building stakeholder trust. In Indonesia, repeated audit failures indicate issues with auditor independence, competence, and knowledge that can undermine public trust. Using a quantitative survey design on 85 auditars from 15 Public Accounting Firms (KAP) in Denpasar Citty, thiss study analyzes the role of these three elements influencing audit quality through instrument tests, classical assumptions, and multiple linear regression. The outcomes reveal that auditor independence, competence, and knowledge have a significant effect on improving audit qualiyt, with an Adjusted R² velue of 0.665, maening they are able to explain 66.5% of the variatian in audit quality, while the remainder is shaped by other factors outside the study. This finding emphasizes the importance of strengthening these three aspects to achieve reliable and high-quality audit practicese.